Anaesthesia and COVID-19: infection control. (July 2020) - Odor, Peter M.; Neun, Maximilian; Bampoe, Sohail; Clark, Sam; Heaton, Daniel; Hoogenboom, Emilie M.; Patel, Anil; Brown, Michael; Kamming, Damon
Summary: The world is currently facing an unprecedented healthcare crisis caused by a pandemic novel beta coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The pathogen is spread by human-to-human transmission via droplets exposure and contact transfer, causing mild symptoms in the majority of cases, but critical illness, bilateral viral pneumonia, and acute respiratory distress syndrome (ARDS) in a minority. Currently, controlling infection to prevent the spread of SARS-CoV-2 is the primary public healthcare intervention used. The pace of transmission and global scale of SARS-CoV-2 infections has implications for strategic oversight, resource management, and responsiveness in infection control. This article presents a summary of learning points in epidemiological infection control from the SARS epidemic, alongside a review of evidence connecting current understanding of the virologic and environmental contamination properties of SARS-CoV-2. We present suggestions for how personal protective equipment policies relate to the viral pandemic context and how the risk of transmission by and to anaesthetists, intensivists, and other healthcare workers can be minimised.